IMPLEMENTATION OF K-MEANS METHOD IN POPULATION GROUPING BASED ON PUBLIC HEALTH INDICATORS OF NORTH SUMATR - Nur Lela; Nurleli; Yolanda Novita Zebua; Mukminah Mardiah; Putri Rahma Novia (Journal of Mathematics and Scientific Computing With Applications, 2021)
Basically, health comes from the word healthy which means well-beingfrom all diseases, both psychological and physical. Health is a source ofstrength for life because of the state of the body that is prosperous andfree from various diseases. Health indicators can be used to determinethe condition of public health in an area. Where there are severalopinions about the variables that make up the Public HealthIndicators. The condition of public health in North Sumatra which isnot homogeneous will make it difficult to develop a healthy city whenconducting monitoring. To eradicate this problem, it is very necessaryto group public health in each city and district. Based on the groupingrequires several methods, the grouping of public health in NorthSumatra in each city and district will be carried out using the K-Meansmethod where this method is very popular and the method is oftenused.The K-Means (Cluster Analysis) method is one of the nonhierarchicalcluster analysis methods that can be used to partition objects Into groups basedon the proximity of characteristics, so that objects that have the same characteristicsare grouped in the same cluster and objects that have similar characteristics. differentgroups are grouped into other clusters. The purpose of clustering is to minimize theobjective function set in the clustering process, which basically seeks to minimizevariation within a cluster and maximize variation between clusters.